2021
DOI: 10.3390/v13020198
|View full text |Cite
|
Sign up to set email alerts
|

Phylodynamics and Codon Usage Pattern Analysis of Broad Bean Wilt Virus 2

Abstract: Broad bean wilt virus 2 (BBWV-2), which belongs to the genus Fabavirus of the family Secoviridae, is an important pathogen that causes damage to broad bean, pepper, yam, spinach and other economically important ornamental and horticultural crops worldwide. Previously, only limited reports have shown the genetic variation of BBWV2. Meanwhile, the detailed evolutionary changes, synonymous codon usage bias and host adaptation of this virus are largely unclear. Here, we performed comprehensive analyses of the phyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 73 publications
(108 reference statements)
0
15
0
Order By: Relevance
“…In this paper, the average values of NYSV, NDV and NLSYV were 55.78, 55.62 and 54.79, respectively, indicating that codon bias was low. The low codon usage bias was also observed in the sugarcane mosaic virus (SCMV), potato virus M (PVM), broad bean wilt virus 2 (BBWV2) and papaya ringspot virus (PRSV) [ 48 , 49 , 50 , 51 ]. Studies have found that low codon usage bias reduces the competition for the synthesis mechanism between viruses and hosts, which is conducive to the expression of viral genes in host cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, the average values of NYSV, NDV and NLSYV were 55.78, 55.62 and 54.79, respectively, indicating that codon bias was low. The low codon usage bias was also observed in the sugarcane mosaic virus (SCMV), potato virus M (PVM), broad bean wilt virus 2 (BBWV2) and papaya ringspot virus (PRSV) [ 48 , 49 , 50 , 51 ]. Studies have found that low codon usage bias reduces the competition for the synthesis mechanism between viruses and hosts, which is conducive to the expression of viral genes in host cells.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent study ( He et al, 2021 ), we employed Codon W software (version 1.4.2) to compute the frequencies of A, T, C, and G at the third positions (A3s, U3s, G3s, C3s) in the synonymous codons. Meanwhile, GC contents at the first (GC1s), second (GC2s), third (GC3s) codon positions, mean of GC1s and GC2s (GC12s) and the frequencies of mononucleotides (A, C, U, and G) were calculated using R Language (version 4.0.4).…”
Section: Methodsmentioning
confidence: 99%
“…3 ). Uracil rich (U-rich) coding sequences were found in the two open reading frames (ORFs) of broad bean wilt virus 2 (BBWV-2) [60] , the cysteine-rich nucleic acid binding protein (NABP) gene of potato virus M (PVM) [63] , P8 protein coding sequences of RBSDV [61] , coat protein (CP) of CTV [54] , cowpea mild mottle virus (CpMMV) [127] and banana bract mosaic virus (BBrMV) [129] ( Fig. 3 C).…”
Section: Nucleotide Composition Of Plant Rna Virusesmentioning
confidence: 99%
“…3 F). For viruses, the AU- or GC-rich composition tends to correlate with their RSCU patterns [60] , [61] , [62] , [63] , [67] , [68] , [132] . For example, an AU-rich composition of SCMV genomes contains codons that frequently end with A and U [62] .…”
Section: Nucleotide Composition Of Plant Rna Virusesmentioning
confidence: 99%
See 1 more Smart Citation